Kepastian Hukum Penerapan Asas Kebebasan Berkontrak Dalam Sebuah Perjanjian Baku Ditinjau Berdasarkan Pasal 1338 Kitab Undang-Undang Hukum Perdata - Susanti, Nia (Indragiri Law Review, 2024)
This research aims to analyse the application of the principle of freedom of contract in standard agreements in Indonesia, particularly in the context of Article 1338 of the Civil Code, which guarantees legal certainty and justice for the parties. The focus of this research is to identify the gap between freedom of contract and the potential injustice arising in standard agreements, especially against parties who have a weaker bargaining position. The method used is normative juridical research with a literature study approach. The results show that the principle of freedom of contract is often limited in standard agreements due to the dominance of the stronger party, which results in inequality in rights and obligations between parties. The conclusion of this research confirms the need for clearer regulations to maintain the balance of rights in standard agreements in order to protect weak parties and prevent exploitation.